Application of DPSIR Framework to Explore Effectiveness of Solid Waste Management in the Maldives. - Shadiya, Fathmath; Shareef, Ali Fawaz (British Journal of Healthcare and Medical Research, 2020)
Waste management in preindustrial times was simple because most of the waste consists of organic materials which decompose naturally. However with the change in consumption patterns of the Maldivians, non- biodegradable synthetic materials such as plastic have become one of the leading causes of marine and coastal pollution in the Maldives. In an attempt to identify a low cost efficient approach of Solid Waste Management system across the country, the Maldivian government has introduced a community based solid waste management system at island level. Hence, the main focus of this study is to explore factors that influence effectiveness of Community Based Solid Waste management systems implemented at island level, using Driver, Pressure, State, Impact, Response (DPSIR) framework. Community participation, community satisfaction level and community willingness to pay for the new system was evaluated in the study. Analysis of data showed, even though most people in the community were satisfied with the new system , there was no association between community satisfaction level and their willingness to pay for the sustenance of the new system. In addition, even though community was aware about plastic pollution, there was no association between community perception about plastic pollution and their willingness to adopt green consumer behaviors. The results also showed that even though majority of community members were satisfied with the current model of waste management system, the current system does not address the driving factors that contributes to solid waste generation at island level.